Characteristics of Epithelial Ovarian Cancer at RSUP Dr. Mohammad Hoesin Palembang Period from January 2020 to September 2023 - Zaen, Wildana Ilmia Uli El Nuha; Agustiansyah, Patiyus; Oktharina, Eka Handayani; Sanif, Rizal; Purnamasari, Septi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: To determine the characteristics of epithelial ovarian cancer patient at Dr. Mohammad Hoesin Palembang General Hospital from January 2020 to September 2023.Methods: This study is a descriptive observational study utilizing secondary data from the Medical Records Department. The inclusion criteria included all patients diagnosed with epithelial ovarian cancer based on anatomical pathology results from the Medical Records Department at Dr. Mohammad Hoesin Palembang Hospital, covering the period from January 2020 to September 2023.Results: A total of 153 patient medical records met the inclusion and exclusion criteria. The results of the study findings revealed that the majority of epithelial ovarian cancer patients were aged 45–59 years (pre-elderly) (51%), had an normal Body Mass Index of 18.5–22.9 kg/m² (57.5%), were most commonly diagnosed at FIGO Stage IIIC (42.5%), had no family history of the disease (98.7%), and were nulliparous (32.7%)Conclusion: Epithelial ovarian cancer patients were predominantly found in the pre-elderly age group, with a normal Body Mass Index, the majority diagnosed at stage IIIC, without a family history, and nulliparous.Karakteristik Kanker Ovarium Epitel di RSUP Dr. Mohammad Hoesin Palembang Periode Januari 2020 – September 2023AbstrakTujuan: Mengetahui karakteristik pasien kanker ovarium epitel di RSUP Dr. Mohammad Hoesin Palembang periode Januari 2020 – September 2023Metode: Penelitian ini merupakan deskriptif observasional menggunakan data sekunder dari Instalasi Rekam Medis. Kriteria inklusi, yaitu seluruh pasien yang didiagnosis kanker ovarium epitel berdasarkan hasil patologi anatomi di Instalasi Rekam Medis RSUP Dr. Mohammad Hoesin Palembang periode Januari 2020 – September 2023.Hasil: Mayoritas pasien kanker ovarium epitel berusia 45 – 59 tahun (pra-lanjut) (51%), Indeks Massa Tubuh normal 18,5–22,9 kg/m2 (57,5%), mayoritas pada stadium IIIC (42,5%), tidak memiliki riwayat keluarga (98,7%), dan nuliparitas (32,7%).Kesimpulan:Penderita kanker ovarium epitel sebagian besar ditemukan pada kelompok usia pra-lansia, dengan ndeks Massa Tubuh normal, sebagian besar berada pada stadium IIIC, tidak memiliki riwayat keluarga, dan nuliparitas.Kata kunci: Kanker Ovarium Epitel, Karakteristik.